Evaluation of a New, Rapid, Fully Automated Assay for the Measurement of ADAMTS13 Activity - Valsecchi, Carla; Mirabet, Maribel; Mancini, Ilaria; Biganzoli, Marina; Schiavone, Lucia; Faraudo, Susanna; Mane-Padros, Daniel; Giles, David; Serra-Domenech, Josep; Blanch, Silvia; Trisolini, Silvia Maria; Facchini, Luca; Rinaldi, Erminia; Peyvandi, Flora (Thrombosis and Haemostasis, 2019)
Thrombotic thrombocytopenic purpura (TTP) is a rare thrombotic microangiopathy (TMA) characterized by the severe deficiency of a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) activity (< 10%). Rapid ADAMTS13 testing is crucial for an early diagnosis and optimal management of acute TTP. We evaluated the performance of the HemosIL AcuStar ADAMTS13 activity assay (Instrumentation Laboratory, Bedford, Massachusetts, United States), a fully automated chemiluminescent immunoassay with an analytical time of 33 minutes. A method comparison study was performed on 176 samples from 49 healthy donors and 127 TMA patients (109 TTP, 7 atypical hemolytic uremic syndrome, 11 other TMAs), comparing this new assay with an in-house FRETS-VWF73 assay and a commercial enzyme-linked immunosorbent assay (ELISA) (TECHNOZYM ADAMTS-13 Activity, Technoclone GmbH, Vienna, Austria). Agreement between methods was assessed with focus on ADAMTS13 activity less than 10%, the medical decision level relevant for TTP diagnosis. The HemosIL AcuStar ADAMTS13 Activity showed good correlation with both the FRETS-VWF73 (r = 0.96) and ELISA (r = 0.96) methods. Slope of the Passing–Bablok regression was 1.05 for FRETS-VWF73 and 1.02 for ELISA, and absolute bias at the medical decision level was +0.1 and +0.3%, respectively. The study also revealed high agreement with FRETS-VWF73 (kappa 0.97) and ELISA (kappa 0.98) methods in classifying TTP patients with a severe deficiency of ADAMTS13 activity. Because of its short turnaround time and full automation, the HemosIL AcuStar ADAMTS13 activity assay might become the assay of choice to rapidly test ADAMTS13 activity in plasma and thus establish the diagnosis of acute TTP in emergency settings.
Keywords: ADAMTS/ADAMTS13; thrombotic thrombocytopenic purpura (TTP/HUS); diagnosis management; autoimmune diseases; chemiluminescent assay